Propozycja pomiaru innowacyjności regionalnej typu INPUT - OUTPUT - Strahl, Danuta; Markowska, Małgorzata (Proposal for Regional Innovation Measurement Input - Output Type, 2007)
The article presents the proposal for regional innovation measurement using the European Innovation Scoreboard indicators. The measurement procedure considers the construction of European regional innovation index INPUT and OUTPUT type. The INPUT index implements variables presented in the EIS and referring to 3 areas: factors stimulating innovations, knowledge creation, innovativeness and entrepreneurship, while in the OUTPUT index there were used variables included in 2 thematic blocks: applications and intellectual property. The presented value of European regional innovation was based on the relation between INPUT and OUTPUT indices, which allowed for the classification of the European regional space into 3 groups of regions. The first group includes regions in which output is smaller than input, while the second one comprises regions in which the relation between input and output takes up values from none of the ranges. The third group covers the regions where output is higher than input. The measure functions in favour of these regions in which the effectiveness of input invested in increasing innovation is better. The proposal is illustrated by an example based on the following variables: the share of employed university graduates in the total population number aged 26-64, the share of population participating in continuing education in the total population number aged 25-64, the number of patents per 1 million of labour force.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 275-286